2019
DOI: 10.1111/wej.12522
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of nanosized amorphous and nanocrystalline TiO2 for photochemical oxidation of methomyl insecticide in aqueous media

Abstract: Aqueous solution loaded with methomyl insecticide is photocatalytically treated upon UV radiation and TiO 2 in a green sustainable oxidation technique. TiO 2 is a highly promising photocatalytic oxidation method, whereas the main findings is increasing the surface area for maximizing the treatment efficiency. Herein, TiO 2 was synthesized via sonochemical hydrolysis technique and amorphous TiO 2 (TM100) was obtained. Further, annealing of amorphous TiO 2 at 500 ºC resulting in anatase phase TiO 2 (TN500). The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 68 publications
0
5
0
Order By: Relevance
“…The results in Fig. (8) demonstrated that the reaction rate under UV illumination was increased with decreasing the initial dye load and the percentage dye removals are 98.9, 29.6, 8.6 % for the initial dye concentrations of 5, 10 and 15 ppm, respectively. This phenomenon of increasing the MB dye removal rate with the initial dye concentration can be related to the increase in the dye color of the polluted water, which may cause a shadowing effect that prevents the UV illumination from penetration the aqueous solution.…”
Section: Effect Of Initial Dye Loadmentioning
confidence: 86%
See 2 more Smart Citations
“…The results in Fig. (8) demonstrated that the reaction rate under UV illumination was increased with decreasing the initial dye load and the percentage dye removals are 98.9, 29.6, 8.6 % for the initial dye concentrations of 5, 10 and 15 ppm, respectively. This phenomenon of increasing the MB dye removal rate with the initial dye concentration can be related to the increase in the dye color of the polluted water, which may cause a shadowing effect that prevents the UV illumination from penetration the aqueous solution.…”
Section: Effect Of Initial Dye Loadmentioning
confidence: 86%
“…The load of the initial MB dye concentration in the aqueous stream on its PANI photo-catalytic oxidation (20 mg/L Pure PANI and 147 mL/min of circulation flow rate) was illustrated in Fig. (8). The results in Fig.…”
Section: Effect Of Initial Dye Loadmentioning
confidence: 98%
See 1 more Smart Citation
“…Modern societies are associated with clean water scarcity due to industrial wastewater release into the aquatic systems that is polluting watercourse as well as the groundwater (Kositzi et al, 2004; Tony et al, 2019; Tony & Mansour, 2020b). Additionally, water demand is becoming a serious problem that should be solved for sustainable societal needs (Zhang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…AOPs are including UV‐based process such as UV/Ozone (Andreozzi et al, 2000), UV/H 2 O 2 (Coelho et al, 2006), UV/Fe 2+ or H 2 O 2 /UV/Fe 2+ (Ashour & Tony, 2020) or may be TiO 2 based systems (Kositzi et al, 2004). Fenton's reagent among AOPs is an effective tool for generating high hydroxyl radicals, OH • , yields (Oller et al, 2011) for a complete mineralization of the toxic contaminants ˙OH with no need for a further treatment (Tony, 2020; Valdez et al, 2012) with a harmless end products, CO 2 and H 2 O (Bauer & Fallmann, 1997; Tony & Mansour, 2019; Tony & Mansour, 2020b). Numerous studies used such reagent for treating various types of effluents, that is, dyes (Papić et al, 2009) (El‐Desoky et al, 2010), polymers in wastewater (Tony & Lin, 2021) paracetamol (Velichkova et al, 2013), phenolic compounds (Babuponnusami & Muthukumar, 2012), antibiotics (Pirsaheb et al, 2019) and p‐chlorophenol (Bao et al, 2019).…”
Section: Introductionmentioning
confidence: 99%